Radial Artery Patency after Trans-radial Cardiac Catheterization in a Bangladeshi Population (University Heart Journal, 2015)
Background: Transradial cardiac catheterization (TCC) is now preferred method over trans-femoral approach globally including Bangladesh. But the incidence of radial artery occlusion (RAO) after TCC is not infrequent and it ranges from 1-18% in different studies. The aim of our study was to see the incidence of RAO after TCC in a population coming for coronary angiogram and/or coronary intervention and also to evaluate the factors responsible for RAO. Methods: The observational prospective study was performed in all consecutive patients coming for TCC. Pre and three month post-procedural modified Allens test, reverse Barbeau test & Duplex ultrasonography for radial artery diameter (RAD), peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistance index (RI) were measured. Results: 69 patients underwent TCC. Mean age was 54 years, 67% were male, 80% hypertensive, 65% diabetic. Follow-up at third month showed one total RAO (1.45%) and mean RAD of the remaining patients was significantly reduced from 2.2+0.03 mm to 2.1+0.03 mm (p=0.001) but none had any symptom or sign of ischemic hand. PSV, EDV & RI were not significantly altered. Reduction of RAD (to